Coexisting Conditions among Children and Adolescents with Cancer in a Section of the South African Private Health Sector: Perspectives from Drug Utilization Data - Marianne N. Otoo; Martie S. Lubbe; Hanlie Steyn; Johanita R. Burger (Springer, 2020)
Coexisting conditions are relatively common in children with cancer, however, there is a paucity of information on the prevalence of coexisting conditions in children with cancer in South Africa. This cross-sectional study aimed at investigating the common coexisting conditions occurring in children and adolescents younger than 19 years undergoing cancer chemotherapy in a section of the South African private health sector. Medicine claims data from 1 January 2008 to 31 December 2017 were queried to identify coexisting conditions using the International Classification of Diseases, Tenth Revision (ICD-10) codes indicated on reimbursed claims. Where ICD-10 codes per claim were non-specific, the pharmacological drug classes of non-cytotoxic medications claimed alongside these codes were categorized using the Monthly Index of Medical Specialties (MIMS) classification system and analyzed using the drug utilization 90% (DU90%) principle. Analysis of sub-pharmacologic drug classes was stratified according to gender and age groups. The reimbursement category of these medicines was noted. Data were analyzed descriptively. A total of 173 participants were included in the study. ICD-10 codes were available for 13.65% (N = 2631) of medicine claims. Diseases of the respiratory system (J00-J99, 7.15%), gastrointestinal tract (K00-K95, 1.60%), and skin disorders (L00-L99, 0.95%) were the most prevalent specific diagnoses identified. Non-specific ICD-10 codes were recorded on 86.35% (n = 2272) of non-cytotoxic medicine claims. The most frequently utilized pharmacological classes of medications included antimicrobial agents (17.40%), respiratory system agents (13.91%), and analgesics (10.64%). As determined from ICD-10 codes and medication claimed on reimbursed claims, children and adolescents being treated for cancers mostly suffered from acute conditions, in particular, microbial infections and diseases of the respiratory system. This indicates the need for the integration of antimicrobial surveillance programs into childhood and adolescent cancer care to curb antimicrobial infections.